The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.3989/scimar.2005.69n4555
|View full text |Cite
|
Sign up to set email alerts
|

Annual reproductive cycle and fecundity of <i>Scorpaena notata</i> (Teleostei, Scorpaenidae)

Abstract: SUMMARY: Scorpaena notata (Teleostei: Scorpaenidae) is an oviparous species with external fertilisation that shows some unusual features in its gonadal morphology and gametogenesis. In this work we analyse the annual reproductive cycle and the fecundity of this species by studying the monthly histological changes in the gonads and of various indices related to reproduction. Sexual dimorphism does not occur in the population we studied, which is clearly dominated by males. Multiple spawning takes place between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 18 publications
5
27
0
Order By: Relevance
“…All females sampled in the present work were in a developing-or spawning-capable maturity stages. The mean GSI value of S. loppei females (6.0 ± 0.3) was similar to that reported for other Scorpaena species during their reproduction period (GSI≈5 for both S. notata and S. porcus; see: Bradai and Bouain 1991, Muñoz et al 2005). Taking into account the values of the GSI and the estimated date of birth of the validated age 0 individual (during September), the reproduction period of S. loppei should occur during late spring-summer , similarly to other Scorpaena species in the area (Bradai and Bouain 1991, Muñoz et al 2005).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…All females sampled in the present work were in a developing-or spawning-capable maturity stages. The mean GSI value of S. loppei females (6.0 ± 0.3) was similar to that reported for other Scorpaena species during their reproduction period (GSI≈5 for both S. notata and S. porcus; see: Bradai and Bouain 1991, Muñoz et al 2005). Taking into account the values of the GSI and the estimated date of birth of the validated age 0 individual (during September), the reproduction period of S. loppei should occur during late spring-summer , similarly to other Scorpaena species in the area (Bradai and Bouain 1991, Muñoz et al 2005).…”
Section: Discussionsupporting
confidence: 63%
“…The mean GSI value of S. loppei females (6.0 ± 0.3) was similar to that reported for other Scorpaena species during their reproduction period (GSI≈5 for both S. notata and S. porcus; see: Bradai and Bouain 1991, Muñoz et al 2005). Taking into account the values of the GSI and the estimated date of birth of the validated age 0 individual (during September), the reproduction period of S. loppei should occur during late spring-summer , similarly to other Scorpaena species in the area (Bradai and Bouain 1991, Muñoz et al 2005). Both, the maturity stage and the lack of relation between GSI and individual total length indicated that all females, including the smallest ones and even the age 0 recruits, such as that sampled in the present work (GSI = 6.1), were probably ready for reproduction in their first year of life.…”
Section: Discussionsupporting
confidence: 63%
“…Despite this length class bias, the majority of the published works showed no deviation from an overall sex ratio of 1 : 1 (Massutí et al 2000, Ordines et al 2009, 2012, Sequeira et al 2009. Curiously, for the small red scorpionfish, Scarcella et al (2011) and Muñoz et al (2005) reported a sex ratio biased in favour of males but no significant differences in length classes by sex. However only 6 females larger than 17 cm were caught in the Adriatic Sea and the larger specimen used by Muñoz et al (2005) had 16.7 cm, suggesting that males are probably larger than females.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the mean GSI value for male S. cardinalis during the spawning season in the present study was 1/40 of the weight of the female values. A similar disparity ow, ovarian wall; vo, vitellogenic oocyte; po, previtellogenic oocyte; os, ovarian stroma; bv, blood vessel; ol, ovarian lumen; p, peduncle; m, mesothelium; ml, muscle layer; el, epithelial layer; sp, secretory processes; ho, hydrated oocyte; of, ovarian fluid. in GSI values between the sexes has been reported for S. notata (Muñoz et al 2005;Ordines et al 2009), where males attained greater sizes and ages than did females in the Mediterranean (Ordines et al 2009). The disparity in the ripe gonad size between the sexes suggests that the males of S. cardinalis use their sperm more efficiently than do those of the congeneric species S. porcus and S. guttata, and so do not require the same level of sperm production.…”
Section: Reproductionmentioning
confidence: 99%
“…It is not known whether this pattern is an artefact of our sampling protocol or whether it reflects a short period when spawning actually occurs. Published monthly GSI values in other Scorpaena congenerics (S. notata, S. guttata and S. porcus) indicate spawning periods of approximately 4 months during which mean GSI values range between ,3 and 5% (Love et al 1987;Muñoz et al 2005;Bilgin and Ç elik 2009). The peak mean GSI values for female S. cardinalis of 2.8% during March 2005 and 4.0% during March 2009 were similar to those reported for other spawning female Scorpaena congenerics; however, the relatively low mean GSI values ( 1%) that occurred for all other months do suggest that spawning may be restricted to a shorter period in S. cardinalis.…”
Section: Reproductionmentioning
confidence: 99%